Implementation Of Next-Generation Firewalls To Protect Applications From Malware Attacks - Herika Andini Putri; Nazel Djibran; Rohmat Tulloh (Publikasi Indonesia, 2023)
Based on the rapid development of technology that has a positive and negative impact; one of the negative impacts is the leakage of data, called cybercrime. To overcome this, in this study, the design of the next-generation firewall (NGFW) protects technology and information systems from threats and malware attacks on technology and information systems. In this study, the Palo Alto firewall is implemented by configuring the firewall and testing the attack using malware. This test's results aim to prevent data loss, material loss, and paralysing of public services. Moreover, it is efficient and effective in scanning for variations of attacks without affecting network performance. The results' implications are expected to solve the problems faced perfectly. NGFW takes precautions by blocking malware access to its network traffic